PEMBUATAN PART BRACKET PIPE MAIN L/SIDE 844A7-I7000 MENGGUNAKAN MESIN STAMPING PRESS - Wansyah, Dani Nur; Dony Susandi (Universitas Majalengka, 2024)
This practical work report explains the process of making the Bracket Pipe Main P/Side 844A7-17000part using a stamping press machine and operating procedures for the stamping press machine at PT Persada Selaras Indonesia. The aim is to find out directly the process of making the Bracket Pipe Main P/Side 844A7-17000 part, and to know how to operate the stamping press machine. The process of making the Bracket Pipe Main P/Side 844A7-17000 consists of several stages starting from checking the material using SPHC-PO, checking the product design, the Stamping Press process with four stages of the production process (blanking, bending 1 and forming, bending 2 and restrike, & Piercing). Apart from that, this report discusses how to operate a stamping press machine starting from the machine inspection stage to setting up the stamping press machine. Through this practical work report, it is hoped that readers will gain insight into the process of making the Bracket Pipe Main P/Side 844A7-17000 and the company's contribution to maintaining product quality.